Towards an Embodied Analysis of the Academic Field. Issue 3 (October 2022) - Hanson, Rebecca; Richards, Patricia
In this introduction to the journal's special issue on Gender, Violence, and the Production of Knowledge we engage with the collected articles to expand conversations on embodiment and research. The issue brings together articles that reflect on gender, race, and violence throughout academic spaces—from teaching to tenure, from field sites to job talks. They contribute to ongoing conversations that interrogate embodied experiences not only in the field but also within the university more generally, including but not limited to experiences of harassment. In short, they exemplify, complicate, and go beyond what we argued in our 2019 book: Harassed: Gender, Bodies, and Ethnographic Research . When read together, the pieces drive forward inseparable conversations on race, gender, and the academy; competency, risk, and pleasure in the field; and embodiment, the aesthetics of resilience, and resistance. Collectively, the articles underscore precisely why attending to embodiment—its pains, its pleasures, its histories and silences—in the field as well as institutional academic spaces is so crucial for the wellbeing of scholars and for the production of transformative knowledge.